Trisulfide linked cholesteryl PEG conjugate attenuates intracellular ROS and collagen-1 production in a breast cancer co-culture model. (24th November 2020) - Dao, Nam V.; Ercole, Francesca; Urquhart, Matthew C.; Kaminskas, Lisa M.; Nowell, Cameron J.; Davis, Thomas P.; Sloan, Erica K.; Whittaker, Michael R.; Quinn, John F.
Abstract : Treatment of cancer cell-fibroblast co-cultures with H2 S-releasing trisulfide conjugate causes restoration of ROS levels in the cancer cells and normalisation of collagen-1 expression in the fibroblasts. Abstract : The progression of cancer has been closely-linked with augmentation of cellular reactive oxygen species (ROS) levels and ROS-associated changes in the tumour microenvironment (TME), including alterations to the extracellular matrix and associated low drug uptake. Herein we report the application of a co-culture model to simulate the ROS based cell–cell interactions in the TME using fibroblasts and breast cancer cells, and describe how novel reactive polymers can be used to modulate those interactions. Under the co-culture conditions, both cell types exhibited modifications in behaviour, including significant overproduction of ROS in the cancer cells, and elevation of the collagen-1 secretion and stained actin filament intensity in the fibroblasts. To examine the potential of using reactive antioxidant polymers to intercept ROS communication and thereby manipulate the TME, we employed H2 S-releasing macromolecular conjugates which have been previously demonstrated to mitigate ROS production in HEK cells. The specific conjugate used, mPEG-SSS-cholesteryl (T ), significantly reduced ROS levels in co-cultured cancer cells by approximately 50%. This reduction was significantly greater than that observed with the other positive antioxidant controls. Exposure to T was also found to downregulate levels of collagen-1 in the co-cultured fibroblasts, while exhibiting less impact on cells in mono-culture. This would suggest a possible downstream effect of ROS-mitigation by T on stromal-tumour cell signalling. Since fibroblast-derived collagens modulate crucial steps in tumorigenesis, this ROS-associated effect could potentially be harnessed to slow cancer progression. The model may also be beneficial for interrogating the impact of antioxidants on naturally enhanced ROS levels, rather than relying on the application of exogenous oxidants to simulate elevated ROS levels.